Pluralizm prawniczy Leona Petrażyckiego a pluralizm etyczny Isaiaha Berlina. Ontologia, metodologia, praktyka prawnicza - Majczyk, Krzysztof Jan (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Psychics, ethics and law are the three main pillars of Leon Petrazycki's scientific interests, which finally became interested in the scientific circles of philosophers, lawyers and Polish sociologists. And rightly so, because the measure of the size of the Nation is the knowledge of his heroes. L. Petrażycki was undoubtedly the hero of Polish logic, ethics and law. The moral imperative of restoring, or rather priming properly, the works of Our Great Countryman in contemporary European logic, ethics and law should depend on substantive comparative reflections on the thoughts, concepts and scientific definitions of L. Petrażycki with the greatest contemporary creators of logic, ethics and law, who were more fortunate to appear in the scientific space than our compatriot. Undoubtedly, Isaiah Berlin is the precursor of European ethical pluralism. I. Berlin is above all Anglo-Saxon ethics, strongly associated with the environment of today's most outstanding philosophers of positivist Anglo-Saxon law. analytical jurisprudence. The family and personal fates of both Petrazycki and I. Berlin are connected with Soviet Russia, which is the epitome of all philosophical trends contrary to both the ethical pluralism of I. Berlin and the legal pluralism proclaimed by L. Petrazycki. Although their views have developed differently, due to the different ethical traditions and especially the dissimilarity of Anglo-Saxon legal culture from the continental legal culture, they can be treated together as a counterpoint to all totalitarianisms of the twentieth century. What's more, there is a kind of complementarity between the ethical thought of I. Berlin and the psychological theory of law of L. Petrażycki, which, despite different ontological assumptions, enormously enriches contemporary European philosophical and legal thought. Because their fates were different, the common knowledge of the ethical pluralism of I. Berlin in Western Europe co-exists with the common ignorance in this cultural circle of legal pluralism of L. Petrazycki. The aim of the paper is to overcome the above-mentioned scientific negligence in relation to the achievements of Our Great Countryman. One can put forward the thesis about the ontological difference of the compared concepts of pluralism. Well, I. Berlin is the epitome of the agnostic culture of Western Europe. The above-mentioned culture published I. Berlin as the creator of ethical pluralism, ie the creator of a cultural current consisting in the existence of mutually co-existent in the spirit of tolerance, individuals, social groups and even nations. Meanwhile, L. Petrażycki, a noble son of the Polish nation tortured by the bondage, observing the developing European national nationalisms that led, during his lifetime, to social revolutions, then to World War I and Fascism and Bolshevism, he proclaimed, though with increasing bitterness, the idea. " love of nations "and the idea of fighting with shallow, cheap legal positivism. In view of the above-mentioned ontological differences, the question arises as to which of the aforementioned cultural concepts leads to the development of ethical and legal culture? A comparison of several basic theses of ethical pluralism of I. Berlin, including the idea of objectively existing but ultimately incommensurable ethical values and their impact on the establishment and application of law with L. Petrazycki's idea of universal love, psychological theory of law and the principles of legal policy will allow to visualize two different ontological perspectives, two different groups of methodological problems with the absorption of ethical values and ethical norms as legal values and legal norms and differences in practical possibilities of using the scientific achievements of the above-mentioned scholars for the development of legal practice as an important element of culture of contemporary societies and European nations in the era of globalization and strong mutual penetration cultures. Unfortunately, empirical ethical experiences and insightful phenomenological analysis reveal the deep ethical divide of modern man associated with his failure to practice rationality. It was only the submission of both theories to the complementary theological and philosophical law of Saint. Augustine reveals their basic cognitive errors of reality, ethical confusion and praxeological ineffectiveness. Using the work of L. Petrazycki and the ethical plurality of I. Berlin criticized against it, the human anthropological concepts resulting from them were constructed and confronted with the ontologically and ethically opposing trinitarian Christian personalism of St. Augustine. A broad argument was made for the thesis of the ceaseless attractiveness of the trinitarian Christian personalism of Saint. Augustine as a concept of the development of personal individuality by every human being, as well as a hopeful perspective for the development of legal and political systems by modern societies, living in a maze of ontologically lost ideologies of global society.